Offline Evaluation and Optimization for Interactive Systems - Li, Lihong (Proceedings of the 8th ACM International Conference on Web Search and Data Mining, 2015)
A tutorial given at WSDM'15, the Eighth ACM International Conference on Web Search and Data Mining, Shanghai, China, February 6, 2015